Oncology Nurse Coordinators in Clinical Trials - Shaking up the Melanoma Team - Hani Steinberg (Elsevier, 2020)
In recent years, melanoma research has undergone a renaissance. The disease that was once viewed, at least in a metastatic setting, as intractable and untreatable is now revealing its molecular "weaknesses." The year 2011 was a landmark year for melanoma therapy, with the introduction of two new agents - the anti-cytotoxic T-lymphocyte-associated protein 4 (CTLA-4) antibody ipilimumab and the BRAF (V-raf murine sarcoma viral oncogene homolog B1) inhibitor vemurafenib. These two agents were shown to confer a survival benefit, which was followed by the approval by the Food and Drug Administration (FDA). In 2014, other immune checkpoint inhibitors, such as pembrolizumab and nivolumab, were approved for the treatment of metastatic melanoma. By 2019, the FDA had also approved pembrolizumab as adjuvant therapy. Target therapy and immunotherapy are now the standard of care for melanoma patients. Clinical trials are currently ongoing for new neoadjuvant therapies. Rapidly evolving knowledge will perhaps downgrade melanoma to the level of a chronic, manageable disease from the intractable "black cancer," it was in the past and a disease that struck fear into the hearts of those who were diagnosed. Changes in immunotherapy treatments were followed by a large volume of clinical trials. This situation has resulted in the need for changes in the roles of existing melanoma multidisciplinary team members, including the clinical trials nurse (CTN). The role of the CTN is not suitable for these new conditions. A new role and tasks need to be established, evolving the CTN into an oncology nurse coordinator (ONC). In this article, we have described the role and responsibilities of an ONC and the changes that have taken place within the multidisciplinary melanoma team.